2022
DOI: 10.1161/jaha.121.024339
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Short‐Term Effects of a Multi‐Component Emergency Department Blood Pressure Intervention: A Pilot Randomized Trial

Abstract: Background Emergency department (ED) visits can be opportunities to address uncontrolled hypertension. We sought to compare short‐term blood pressure measures between the Vanderbilt Emergency Room Bundle (VERB) intervention and usual care plus education. Methods and Results We conducted a randomized trial of 206 adult patients with hypertension and elevated systolic blood pressure (SBP) presenting to 2 urban emergency departments in Tenne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Our results help elucidate how truly complex the nature of engagement is. Although our past work and that of others have demonstrated the importance of behaviorally interacting with mHealth interventions [ 9 , 31 , 40 , 41 ], this measure represents one piece of a larger puzzle. Engagement may be best conceptualized as including both a behavioral dimension and a cognitive dimension.…”
Section: Discussionmentioning
confidence: 99%
“…Our results help elucidate how truly complex the nature of engagement is. Although our past work and that of others have demonstrated the importance of behaviorally interacting with mHealth interventions [ 9 , 31 , 40 , 41 ], this measure represents one piece of a larger puzzle. Engagement may be best conceptualized as including both a behavioral dimension and a cognitive dimension.…”
Section: Discussionmentioning
confidence: 99%
“…The higher intensity mHealth components were not associated with a greater decline in BP. Hypotheses for the lack of BP difference among the mHealth components include (1) variable engagement with prompted SMBP monitoring, 15% of participants did not text any BPs; (2) access to care barriers outside of scheduling and transportation were not well addressed 28 as evidence by a greater reduction in BP among those taking antihypertensives, (3) no true difference between components. Furthermore, BP reductions were less among Black participants than non-Black participants, requiring further study.…”
Section: Discussionmentioning
confidence: 99%
“…The successful completion of this trial and other ED-based hypertension trials suggests that further efforts to engage the ED in chronic disease management of patients at high risk for cardiovascular disease are warranted. 28,31 Second, Reach Out SMBP monitoring relied on readily scalable text messaging rather than smartphone application-based SMBP monitoring. Notably, a recent study has been shown to have no additional benefit of application-based SMBP monitoring over standard monitoring.…”
Section: Discussionmentioning
confidence: 99%